Inhibition of growth and metastasis of breast cancer by targeted delivery of 17-hydroxy-jolkinolide B via hyaluronic acid-coated liposomes. (1st April 2021) - Liu, Dan; Zhang, Qi; Wang, Jing; Guan, Shuang; Cai, Defu; Liu, Jicheng
Graphical abstract: Highlights: Liposome encapsulation overcomes low aqueous solubility of 17-Hydroxy-jolkinolide B. Hyaluronic acid modification enhances the targeting abilities of liposomal drugs. The modified liposomal drugs suppress breast cancer metastasis by inhibit EMT process. Abstract: Hyaluronic acid (HA)-coated liposomes were designed for the targeted delivery of 17-hydroxy-jolkinolide B (HA-Lip-HJB). HA-Lip-HJB had a particle size of 130.8 ± 1.9 nm, zeta potential of -52.36 ± 1.91 mV, and encapsulation efficiency of 89.2 ± 1.5 %. In vitro cell experiments indicated that modification of HA-Lip-HJB increased its cytotoxicity and cellular uptake via CD44 receptor-mediated endocytosis pathway. Of particular importance is that HA-Lip-HJB suppressed cell migration and invasion by inhibiting epithelial-mesenchymal transition (EMT) process. Moreover, the HA-Lip-HJB displayed notable growth inhibition on tumor spheroids. Furthermore, in vivo tissue distribution and anti-tumor experiments carried on BALB/C mice bearing 4T1 tumor indicated that HA-Lip-HJB had strong tumor targeting and tumor suppression abilities. The results also demonstrated that HA-Lip-HJB inhibited tumor cells migration and colonization on the lung. Therefore, HA-Lip-HJB is a promising formulation for metastatic breast cancer therapy.